Peran Influencer Dalam Mempromosikan Artelio Florist melalui Instagram Story - Ni Ketut Iswarini; Ni Putu Diah Arista Dewi; Ida Ayu Sri Puspa Adi (Journal of Hospitality Accommodation Management (JHAM), 2023)
The purpose of this study is to find out how the role of influencers in promoting Artelio Florist through Instagram stories so that it can be used as a reference for Artelio Florist to use influencers or not in the future. The research method used was observation and interviews, then the data obtained were analyzed using qualitative descriptive methods. Based on the AISAS flow, which uses two samples from micro-influencers, it is able to produce good insight, even though it is not optimal. The uploaded content is noticed by many people and some of them are interested and seek information by following and visiting Artelio Florist's account. Not only that, some of them decided to make a purchase and share the content with other users if they need a reference on where to buy flower arrangements. It is recommended that Artelio florist be more active in uploading content in the form of videos or photos through the Instagram story feature.